Analisis Peran Strategi Komunikasi dalam Fundraising LAZIS Al-Haromain - firnanda, Aprilia Ayu; Ajid Baldan Amin; Siti Faridatu Aldawiyah (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
Abstract: Lembaga Amil Zakat (LAZ) has a strategic role in managing social funds, where the success of fundraising is largely determined by the quality of communication strategies. This study aims to analyze the role of communication strategies in LAZ Al Haromain's fundraising activities, focusing on communication patterns, channels used, and their impact on fundraising. The research method uses a descriptive qualita-tive approach with a case study at LAZ Al Haromain. Data collection techniques were conducted through in-depth interviews, observation, and documentation studies. Informants were selected purposively, including the head of the institution, the fundraising team, and a number of donors. The results showed that LAZ Al Haromain developed a fundraising communication strategy through three main approaches: (1) Personal communication through relationships and social networks, (2) Utilization of digital media and social plat-forms, and (3) Creation of persuasive narratives based on social impact. The communication channels used include social media, websites, online fundraising platforms, and direct communication through socializa-tion and friendship activities. In-depth analysis reveals that communication strategies play a significant role in increasing donor trust, mobilizing social participation, and encouraging growth in the volume of funds raised. Factors such as institutional credibility, reporting transparency, and the ability to communicate so-cial impact are key to successful fundraising. The research concluded that LAZ Al Haromain's communica-tion strategy has integrated traditional and digital approaches comprehensively. Research recommenda-tions include developing more innovative communication strategies, increasing digital capacity, and strengthening social impact narratives to encourage donor participation.